2017
DOI: 10.1039/c6gc03141b
|View full text |Cite
|
Sign up to set email alerts
|

Highly chemoselective reduction of nitroarenes over non-noble metal nickel-molybdenum oxide catalysts

Abstract: A non-noble Ni-MoO3/CN@SBA-15 catalyst exhibits unprecedented catalytic activity and chemoselectivity for the reduction of nitroarenes to anilines in ethanol with hydrazine hydrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…[1][2][3] In particular, the catalytic hydrogenation of nitroarenes with supported catalysts is aw idely accepted strategy,d ue to the easy separation of the product and recovery andr ecyclability of catalyst. [10] Li and co-workers reported B/N-codoped graphene-like carbon as an efficient metal-free catalyst for the hydrogenation of nitroarenes. [4][5][6][7][8] For example, Doherty et al reported phosphine-decorated, polymer-immobilized, ionic-liquid-stabilized palladium nanoparticles (NPs) for highly efficient hydrogenation of nitroarenes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] In particular, the catalytic hydrogenation of nitroarenes with supported catalysts is aw idely accepted strategy,d ue to the easy separation of the product and recovery andr ecyclability of catalyst. [10] Li and co-workers reported B/N-codoped graphene-like carbon as an efficient metal-free catalyst for the hydrogenation of nitroarenes. [4][5][6][7][8] For example, Doherty et al reported phosphine-decorated, polymer-immobilized, ionic-liquid-stabilized palladium nanoparticles (NPs) for highly efficient hydrogenation of nitroarenes.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Wang and co-workers fabricated heterogeneous nonnoble metal nickel-molybdenum oxide catalystss upported on ordered mesoporous silica SBA-15t hat exhibited excellent catalytic activity for catalytic hydrogenation of nitroarenes with hydrazineh ydrate as hydrogen donor. [10] Li and co-workers reported B/N-codoped graphene-like carbon as an efficient metal-free catalyst for the hydrogenation of nitroarenes. [11] However, most of the reported noble-metal-based catalysts are expensive and not suitable for large-scale application.M oreover,t he non-noble metal catalysts and metal-freec atalysts often need complexp reparation procedures and harshh ydrogenationr eaction conditions, including high hydrogen (H 2 ) pressure and high reactiont emperatures.M oreover,a lthough molecular H 2 as the hydrogen source is atom-economic, it is explosive and requires careful transportation and storage.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Huang et al. investigated Ni‐MoO 3 /CN@SBA‐15 catalyst for reduction of nitro compounds using excess NH 2 NH 2 as a reductant but from economic and recovery viewpoint hydrazine is hazardous chemical to recover from the reaction media if it is not used in stoichiometric amount for catalysis . Giri et al.…”
Section: Introductionmentioning
confidence: 99%
“…Of late, more and more studies on metal NPs supported on a recyclable polymer‐supported palladium catalyst, such as graphene oxide or graphene, have been reported for the reduction of nitroarenes. However, the nano‐M@PANIs materials are not widely accepted for the reduction of nitroarenes, since the reactions require to use of excessive amounts of NaBH 4 and additional organic auxiliaries . Moreover, using large amounts of metal as a catalyst leads to heavy‐metal contamination and very low TON values .…”
Section: Introductionmentioning
confidence: 99%